“Click” Chemistry for Biosensors - Ömeroğlu, İpek; Öztürk, Dilek; Durmuş, Mahmut Esad (CRC Press, 2024)
“Click” chemistry is used for molecular fitting in the widest possible range of applications impacts practically all branches of chemical science. It is a series of chemical reactions that efficiently and rapidly combine small units with heteroatom bonds to form stable new substances. This chemical reaction is mostly used in the modification of biomolecules because it provides advantages such as mild reaction conditions and high synthesis efficiency, fast reaction, and high selectivity. Biosensors are based on the interaction between a molecular probe with a specific affinity and the target analyte. Also, they can be classified as electrochemical, optical, piezoelectric, thermal, etc. according to the measurement method. Biosensors are miniature devices that can replace heavy, difficult-to-use, special, and complex devices that require specialists in industry and clinical studies according to the advancement of technology. Multifunctional materials developed with the advantages of “click” chemistry are also widely used as biosensors. The materials used in biosensors are modified to increase their selectivity and specificity using the “click” chemistry. In this chapter, information about the developed biosensor materials prepared by “click” chemistry and their responses and functionalities will be discussed. © 2024 Elsevier B.V., All rights reserved.